Managing Cross-Border Projects Towards More Resilient Cooperation in Borderlands. The Post-Pandemic Perspective - Kurowska-Pysz, Joanna; Medeiros, Eduardo; Böhm, Hynek (Logos Verlag Berlin, 2024)
The authors of this monograph were driven to delve into the challenges facing cross-border cooperation amidst crises and disruptions spurred by the adverse impacts witnessed during the COVID-19 pandemic. This included challenges to the implementation of cross-border projects, the activities of Euroregions, and the development of partnerships based on INTERREG programs, as well as other issues related to territorial cooperation. The confluence of the pandemic crisis and broader international geopolitical issues, such as illegal migration to the EU and geopolitical tensions like Russian aggression against Ukraine, underscores the imperative to explore new research avenues focused on bolstering the resilience of cross-border cooperation within the EU. With a focus on identifying key factors shaping the management of cross-border projects co-financed by INTERREG programs, as well as factors influencing partner cooperation, this study aims to fortify cross-border cooperation in the face of future crises and disruptions. The monograph offers valuable insights for institutions and organizations operating in border regions, catering specifically to theoreticians and practitioners engaged in cross-border cooperation. By distilling lessons learned from the COVID-19 pandemic period, it provides a roadmap for integrating resilience into future cross-border activities and endeavours.